2022
DOI: 10.3390/ijms23073504
|View full text |Cite
|
Sign up to set email alerts
|

Metallodrugs: Mechanisms of Action, Molecular Targets and Biological Activity

Abstract: The research interest in the field of inorganic medicinal chemistry had a large increase after the serendipitous discovery of the cytotoxic activity of cisplatin by Rosenberg at the end of 1960s [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
0
3
0
Order By: Relevance
“…Nowadays metallodrugs are important competitors of the conventional purely organic agents due to several important inherent advantages, such as structural diversity, accessible redox states, a broad spectrum of coordination numbers and geometries, and the possibility to fine-tune both the thermodynamics and kinetics of ligand substitution. 1,2 Since the discovery of the remarkable anticancer properties of cisplatin, 3 huge efforts have been devoted to the identification of improved anticancer metallodrugs. In this context, beyond platinum, several other transition metals have been exploited for the synthesis of complexes characterized by a variety of geometries and oxidation states in an attempt to (1) design metal compounds with enhanced pharmacokinetic and pharmacodynamic profiles, and (2) overcome limitations of platinum-based chemotherapy such as heavy side effects and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays metallodrugs are important competitors of the conventional purely organic agents due to several important inherent advantages, such as structural diversity, accessible redox states, a broad spectrum of coordination numbers and geometries, and the possibility to fine-tune both the thermodynamics and kinetics of ligand substitution. 1,2 Since the discovery of the remarkable anticancer properties of cisplatin, 3 huge efforts have been devoted to the identification of improved anticancer metallodrugs. In this context, beyond platinum, several other transition metals have been exploited for the synthesis of complexes characterized by a variety of geometries and oxidation states in an attempt to (1) design metal compounds with enhanced pharmacokinetic and pharmacodynamic profiles, and (2) overcome limitations of platinum-based chemotherapy such as heavy side effects and resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that non-Pt metal compounds have become promising new chemotherapeutic drugs for avoiding the resistance of cancer cells to Pt-based drugs because of their greater effectiveness, less toxicity, and targeting specificity. 7–10 In addition, multitarget metal compounds are also among the most effective strategies to overcome the drug resistance of cancer cells. 11–13 Therefore, designing a novel non-Pt compound based on multiple anticancer mechanisms may be promising for overcoming the resistance of tumor cells to Pt-based drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Metal complexation of well-established drugs constitutes a promising strategy to overcome loss of medication sensitivity and induced resistance [28]. Apart from the important biological activity of the metal ions, administrated in the form of approved metallodrugs [29][30][31][32][33], organometallic chemistry allows wider diversity in the design of medically relevant molecules, notably through higher number of possible geometries, redox features, non-covalent bonding and catalytic properties [29]. Moreover, the coordinated derivatives of biologically active ligands have been known to show synergistic effect with certain metal cores.…”
Section: Introductionmentioning
confidence: 99%